Buka Tutup Gorden Otomatis Dengan Penerapan Arudino Uno - Dea Sylvia Saragih, Yessy; Karima Indah, Sarah (CV RIFAINSTITUT, 2023)
The aim of carrying out this research is to make human work easier by using technological developments, namely the Arduino Uno, in the form of implementing an automatic curtain opening and closing system. The method used in this research is to design a program using the Arduino Uno application and design the tool, ending with testing the design results. From this research, an automatic curtain opening and closing system was produced which was controlled by the Arduino Uno program. With the development of this technology, it can make it easier for humans to control and manage without experiencing difficulties. As before, without this technology, opening and closing the curtains becomes difficult to reach because they are too high, making things uncomfortable. From this research, the output voltage from the Arduino Uno is produced with a range of 4.8 V-4.9 V.